Analisis Peran Financial Technology dalam Meningkatkan Keuangan Inklusif pada UMKM di Kabupaten Banyumas - Chusnul Maulidina Hidayat; Lina Fatimah Lishobrina; Maliana Puspa Arum (International Forum of Researchers and Lecturers, 2023)
The development of information technology supported by the rapid use of the Internet has created a number of fintechs that will make it easier for people to access financial services digitally. The aim of this research is to know the role of fintech against financial inclusion in UMKM in Banyumas. This research uses the method of literature study, by exploring and examining the results of previous research findings. The results of this research explain that financial technology can have a positive impact in increasing inclusive finance on UMKM in Banyumas.